Spatial variation of microplastic abundance and types in Bitung coastal waters, North Sulawesi: influence of fishing, residential, and port activities - Rimper, Joice; Warouw, Veibe; Sangari, Joudy; Uniplaita, Dominique; Lasut , Markus (Universitas Sam Ratulangi, 2025)
Microplastic contamination in coastal waters is shaped by local human activities and hydrodynamic transport, yet spatially explicit evidence from many Indonesian coastal cities remains limited. This study assessed the spatial variation of microplastic abundance and morphological types in Bitung coastal waters, North Sulawesi, across three stations representing contrasting coastal activity zones: fishing area (Station 1), residential area (Station 2), and port area (Station 3). Surface-water samples were collected in July 2025 using horizontal plankton-net tows over a 10 m transect, with three replicates per station. Laboratory processing included sequential sieving (0.4 mm and 5 mm), oven drying (90°C, 24 h), wet peroxide oxidation (WPO) with fenton reagent, NaCl density separation, and filtration (Whatman 100–250 µm), followed by microscopic classification into fiber, fragment, pellet, film, and foam types. A total of 488 microplastic particles were recorded across all samples. The port station showed the highest abundance (320 particles, mean 106.7 ± 10.2 particles per tow), substantially exceeding fishing (92 particles, 30.7 ± 6.4) and residential (76 particles, 25.3 ± 9.5) stations. Overall composition was dominated by fragments (41.8%) and fibers (35.7%). Type composition differed significantly among stations, with fragments strongly dominating the port station, whereas fibers dominated the fishing and residential stations. These patterns indicate distinct local sources (e.g., shipping/port operations and packaging debris vs. textiles and fishing gear), highlighting the need for targeted waste control and monitoring in Bitung’s coastal zones.